GEOTHERMAL EXPLORATION IN THE ALEXANDRIA AREA, THESSALONIKI BASIN (MACEDONIA, NORTHERN GREECE) - Arvanitis, A.; Kolios, N.; Ntokos, D. (Bulletin of the Geological Society of Greece, 2016)
The area of Alexandria is located in the Thessaloniki basin that has been filled with more than 4 km of sediments. In 1980, oil exploration borehole AL-1, 1,705 m deep, was drilled north of the town of Alexandria and the temperatures of 39 and 65oC were recorded at depths of 700 and 1,705 m respectively. During 1996-2000, two geothermal exploration boreholes were drilled at depths of 532 and 620 m penetrating Quaternary and Pliocene sediments and the temperatures of 30.1 and 33.4oC were measured at 500 and 611 m respectively. The preliminary geothermal investigation resulted in the construction of the first production well (GN-1P). It was drilled to a depth of 805 m penetrating clays, sands, tuffs, marls, clayey marls, marly limestones, gravels, sandstones and conglomerates. The borehole was cased down to 805 m and screens were placed at various depths below 607 m. Temperature and electrical conductivity values of 35.1-37.2oC and 5,100-8,200 μS/cm respectively were recorded at depths of 607-800 m. This well discharges 30-40 m3/h waters at 34.1oC with artesian flow and provides 130 m3/h waters at 35.5oC with pumping. The produced geothermal water with TDS of 2.18 g/l belongs to the Na-Cl type differentiated from the shallow waters. The thermal capacity of well GN-1P is calculated to be 1.65 MWt.